Analisis Pelayanan Angkutan Umum Minibus Bagong Trayek Landungsari – Jombang - Matilda Hasri; Pamela Dinar Rahma; Blima Oktaviastuti (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2021)
The basis of analysis of public transport service is the existence of optimal services such as convenience,fast and easy. This is taken into consideration to determine the level of service of public transport. The purpose of this study was to determine the characteristics, performance and service level of the Bagong minibus public transportation on the Landungsari-Jombang ruote. The method used is the load factor calculation analysis method,travel speed,headaway,travel time,service time,number of vehicles,passenger waiting time,start and end of service. The results of the study are load factor 0,38%, speed 37,5 km/hour, headaway 48,3 minutes, travel time 1,6 minutes/km, Service time 13 hous,number of vehicles 0,27%,passenger waiting time 24,15 minutes,initial and end of service 05-18 hours. From the result of the recapitulation of the performance result of the bagong minibus public transportation, it can be concluded that the level of service has moderate criteria.